2013
DOI: 10.1002/acp.2939
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Sexual and Nonsexual Television Commercials as a Function of Viewing Context and Viewer Gender

Abstract: The present study investigated memory for sexual and nonsexual commercials as a function of programme-commercial congruity and programme-induced level of involvement. Participants were allocated to one of four conditions: sexual programme with sexual or nonsexual commercials and nonsexual programme with sexual or nonsexual commercials. Recall and involvement levels were tested with a series of memory tests and programme ratings. It was predicted that sexual advertisements would be recalled and recognised bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 39 publications
10
32
2
Order By: Relevance
“…Bushman and Bonacci's () findings were challenged by Fried and Johanson (), on the grounds that they did not adequately control for potential confounding factors in the programme content, such as the programme nature and humour. Fried and Johanson () found that sexual programmes did not reduce viewers' memory for the advertisements when the programme nature and humour were controlled, as also shown by later studies (see King et al, ; Leka et al, ).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Bushman and Bonacci's () findings were challenged by Fried and Johanson (), on the grounds that they did not adequately control for potential confounding factors in the programme content, such as the programme nature and humour. Fried and Johanson () found that sexual programmes did not reduce viewers' memory for the advertisements when the programme nature and humour were controlled, as also shown by later studies (see King et al, ; Leka et al, ).…”
Section: Introductionmentioning
confidence: 63%
“…Although earlier research provided evidence for the effectiveness of programme–advertisement congruence on advertisement recall (Leka et al, ), the majority of our recent studies have failed to find such an effect (Furnham & Hiranandani, ; Furnham & Mainaud, ; King et al, ; Leka et al, ). The lack of a programme–advertisement congruence effect on advertisement recall may be explained by the difference in proximity between the sexual scenes in the programme and the advertisements.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations